2006
DOI: 10.1196/annals.1354.017
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Differentially Expressed Genes in the Ventricular Myocardium of Senescent Rats

Abstract: Aging alters a variety of physiological functions of the heart. The molecular basis of the age-related functional changes has not been fully understood. Differential gene expression provides the basis for many fundamental cellular processes associated with development and aging. The identification and cloning of genes whose expression is modulated by aging can be of importance for our better understanding of these age-related phenomena. In order to isolate and characterize gene products differentially expresse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…The specific regulatory control of ATP5MC genes remains unstudied, but expression assays suggest that the expression levels of ATP5MC1, 2, and 3 respond independently when exposed to the same stressor. [34][35][36][37][38][39][40] Differential expression patterns for ATP5MC genes within the nervous system (eg, striatum vs. spinal cord) or resulting from environmental factors such as oxidative stress [39][40][41][42] might increase the proportion of mutant ATP5MC3, influencing the phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…The specific regulatory control of ATP5MC genes remains unstudied, but expression assays suggest that the expression levels of ATP5MC1, 2, and 3 respond independently when exposed to the same stressor. [34][35][36][37][38][39][40] Differential expression patterns for ATP5MC genes within the nervous system (eg, striatum vs. spinal cord) or resulting from environmental factors such as oxidative stress [39][40][41][42] might increase the proportion of mutant ATP5MC3, influencing the phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…Aging is associated with higher endogenous ET-1 levels (mRNA and protein) in both plasma and vascular tissue in males and females (10,36,53,57) together with an altered ET A to ET B ratio (48). Functionally, an increase in ET-1-dependent vascular tone has been demonstrated in clinically healthy older men (99).…”
Section: Endothelin System In Agingmentioning
confidence: 97%
“…In old mice, ET-1 receptor A signalling suppresssed EDD [ 28 ]. Indeed, elevated endogenous ET-1 mRNA and protein levels in plasma and vascular tissue have been associated with ageing in both female and male rats [ 180 , 181 ]. In studies with aged mice and rats, they observed ET-1 dampened vasoconstriction (albeit increased ET-1 concentrations) potentially due to functional inability of endothelin receptor signalling pathways [ 179 , 182 , 183 ].…”
Section: Et-1 Age and Ageing: Is Differential Diagnostic Approach Feasible?mentioning
confidence: 99%